Effect of treating the larval stage of the large waxworm Galleria mellonella with different concentrations of zinc oxide nanomaterials ZnO, titanium dioxide TiO2 and Bacillus thuringiensis spores on some aspects of the insect's life. - Duaa Ali; Adnan Mohammed (College of Education for Pure Sciences, 2022)
Abstract The present study was conducted to determine the impact of nanoparticles (TiO2 and ZnO) at concentrations (100,500,1000,5000) ppm and Bacillus thuringiensis spores at concentration (106 and109 cells/ml of D.W on some biological aspects of greater ,108 107 wax moth(Galleria mellonella) . The results showed that these materials have a significant effect on the development stages, larva and pupa of Galleria mellonella .The nanoparticles had a clear effect on the motility of the insect as high concentrations, 5000ppm of ZnO increased the killing rate in the larva and pupa to 80.10% and 34.64 respectively. Treatment with these materials also had a significant effect in some biological aspects of the first generation. The average number of eggs was 22.667 and 10.007 in the treatment with concentration 5000ppm of both TiO2 and ZnO respectively, while the average number of egg was 9.667 in the treatment with 106 of Bacillus thuringiensis spores . Treatment with concentration 5000ppm also caused a delay in the eggs laying of the greater wax moth to reach 87.720 and 95.163% of both, TiO2 and ZnO respectively, compared with Bacillus thuringiensis spores with showed 94.233% at106 concentration